2013
DOI: 10.1371/journal.pone.0081200
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of and Attitudes to Influenza Vaccination in Healthy Primary Healthcare Workers in Spain, 2011-2012

Abstract: Annual influenza vaccination is recommended for healthcare workers, but many do not follow the recommendation. The objective of this study was to investigate the factors associated with seasonal influenza vaccination in the 2011–2012 season. We carried out an anonymous web survey of Spanish primary healthcare workers in 2012. Information on vaccination, and knowledge and attitudes about the influenza vaccine was collected. Workers with medical conditions that contraindicated vaccination and those with high ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
24
0
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 44 publications
9
24
0
5
Order By: Relevance
“…Although the ideal vaccination rate among healthcare providers is 100%, different studies have suggested that vaccination rate of 80% or more of healthcare providers are considered sufficient to reduce transmission and provide herd immunity in a safe level within healthcare facilities. 9 In our study, the vaccine coverage among healthcare providers (53.4%) was similar to previously reported rates in other studies such as in Spain 50.7% coverage, 10 and in Austria 52% coverage. 11 43.9% of participants who have received the vaccine were having co-morbidities.…”
Section: Discussionsupporting
confidence: 91%
“…Although the ideal vaccination rate among healthcare providers is 100%, different studies have suggested that vaccination rate of 80% or more of healthcare providers are considered sufficient to reduce transmission and provide herd immunity in a safe level within healthcare facilities. 9 In our study, the vaccine coverage among healthcare providers (53.4%) was similar to previously reported rates in other studies such as in Spain 50.7% coverage, 10 and in Austria 52% coverage. 11 43.9% of participants who have received the vaccine were having co-morbidities.…”
Section: Discussionsupporting
confidence: 91%
“…In this multiseason study of adults working in acute care hospitals in Canada, the odds ratio for influenza vaccine uptake increased exponentially with every additional year of influenza vaccine uptake over the previous three seasons. Similar findings have been illustrated in studies from the USA, Europe and China, suggesting that the individual perceptions associated with vaccine acceptance and refusal remain stable over several years. It is likely necessary to tailor immunization programs differently to reach HCW at all levels of uptake, from refusers to those accepting influenza vaccine intermittently to those vaccinated annually.…”
Section: Discussionsupporting
confidence: 85%
“…Some studies that include non-hospital workers have shown that vaccination coverages increase with age [24,[31][32][33]. In a previous study that assessed the factors associated with influenza vaccination of HCW using logistic regression methods, we found that age ≥45 years was associated with influenza vaccination [34].…”
Section: Discussionmentioning
confidence: 63%
“…Other commonly-used statistical methods, such as regression models, evaluate the association between explanatory or independent variables and an outcome or dependent variable [34]. In contrast, the combination of MCA and CA aided identification of different types of physicians without using any specific outcome.…”
Section: Discussionmentioning
confidence: 99%